Teaching Speaking Skills Using Puppet Theater Media at the Elementary Level at Dar al-Lughah and Islamic Studies Institute, Seninan Akor, Palengaan, Pamekasan - Moh. Supriyadi; Muhammad Supriyadi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
In Darul Lughah wad dirasatil islamiyah, it is one of the concentrated institutes that teach Arabic to non-native speakers. All students speak Arabic and it is forbidden to speak anything else. There is no exaggeration in it that teaches the Arabic language, communication on the four language skills, and it also teaches vocabulary, conversation, reading, writing, listening, speaking, grammar, and so on. Teachers used several methods of teaching language skills, including using puppet theater, which is achieved in teaching the skill of speech. The objectives of the research are: (1) Teaching the skill of speech by means of puppet theater for the elementary stage at the Darul Lughah wad dirasatil islamiyah (2) The influencing factors in teaching the skill of speech by means of puppet theater for the primary stage at the Darul Lughah wad dirasatil islamiyah The researcher uses the curriculum with qualitative and genre input in the field, and data sources in this research study this teaching, and students who participate in this teaching, then the director of the Darul Lughah wad dirasatil islamiyah. The method used to collect the data is the standardized interview, observation, history and documents. The method used in data analysis is the descriptive analytical study method. The result of this research is the use of puppet theater in teaching the skill of speech for the elementary stage at the Darul Lughah wad dirasatil islamiyah that includes objectives, steps, methods, evaluation, and material. The factors affecting this teaching consist of two parts, including: linguistic and non-linguistic.